O regime jurídico dos incentivos fiscais - Gomes, Denis Vieira (2019)
This essay is focused on the study of tax incentives under the viewpoint of Tax Law. The Brazilian Governmental Entities – States, Federal District and Municipalities – have granted tax incentives in order to lure and retain investments in their territories. Considering that there are States and Municipalities that have more economic power than others, a way to diminish this inequality is for the disadvantaged Govermental Entity to use legal mechanisms focused on attracting investments to its territory. By doing so, each component of the Country's System will aim to correct their own economic inequalities. The Union for example appear in the political scene granting benefits in order to encourage certain activities in which Brazil can’t compete with other countries, or yet, in order to socially enhance a specific region. Member States grant tax incentives for ICMS (Tax on Circulation of Goods and Services) so that companies are incorporated and generate working places in their territory and indirectly enhance tax collection. Tax incentives appear to Governmental Entities as an “counter-tax” alternative tool with which these entities abstain from collecting taxes and diminish the public revenue in exchange for other economic alternatives. Although this may be considered a recurring subject in legal doctrine, this paper will seek to demonstrate that tax incentives have their own peculiar legal regime that should be studied by those who are concerned about this subject